2021
DOI: 10.3390/cancers13163999
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dynamics during Chemotherapy in Epithelial Ovarian Cancer Patients Are Related to Therapeutic Outcome

Abstract: Epithelial ovarian cancer (EOC) is one of the most lethal and silent gynecological tumors. Despite appropriate surgery and chemotherapy, relapse occurs in over half of patients with a poor prognosis. Recently, the gut microbiota (GM) was hypothesized to influence the efficacy of anticancer therapies, but no data are available in EOC. Here, by 16S rRNA gene sequencing and inferred metagenomics, we profiled the GM of EOC patients at diagnosis and reconstructed its trajectory along the course of neoadjuvant or ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 65 publications
0
42
2
Order By: Relevance
“…Indeed, several reports show that alpha diversity is usually higher in normal tissues and benign lesions when compared with tumor. 35 , 36 , 37 , 38 Moreover, higher alpha diversity is often associated with prolonged overall survival in cancer patients 39 , 40 , 41 , 42 ; however, we did not observe significant differences between LR and HR/MET GISTs, which generally show shorter overall survival. 43 …”
Section: Discussioncontrasting
confidence: 70%
“…Indeed, several reports show that alpha diversity is usually higher in normal tissues and benign lesions when compared with tumor. 35 , 36 , 37 , 38 Moreover, higher alpha diversity is often associated with prolonged overall survival in cancer patients 39 , 40 , 41 , 42 ; however, we did not observe significant differences between LR and HR/MET GISTs, which generally show shorter overall survival. 43 …”
Section: Discussioncontrasting
confidence: 70%
“…We found that patients in the mild ARIE subgroup had significantly higher abundances of Roseburia , Veillonella , Prevotella_9 , Megasphaera , and Ruminococcus_2 , genera associated with the production of short-chain fatty acids (SCFAs) ( de la Cuesta-Zuluaga et al, 2017 ; Louis and Flint, 2017 ; D’Amico et al, 2021 ), including butyrate, propionate, and acetate. Many studies have examined butyrate due to its anti-inflammatory and anti-cancer effects.…”
Section: Discussionmentioning
confidence: 96%
“…This means that an imbalance in GM diminishes the original protective effect and promotes the development of colorectal cancer ( 14 ). Also, GM may affect the efficacy of drugs during cancer treatment by targeting the immune response and disrupting the chemotherapeutic drug sensitivity ( 15 , 16 ). At present, immunotherapy for cancer is a major hot topic in cancer treatment.…”
Section: Intestinal Microecologymentioning
confidence: 99%
“…The advert effects of chemotherapy on GM, e.g. dysbiosis, are more prevalent in patients ( 16 ) and animal ( 40 ) models bearing ovarian cancers. In addition, compared to platinum-sensitive patients, platinum-resistant patients showed a more pronounced dysbiosis of GM, with a decrease in the health-related groups and an increase in the proportion of lactic acid-producing bacteria including Coriobacteriaceae and Bifidobacterium ( 16 ).…”
Section: Gynecologic Malignancies and Gmmentioning
confidence: 99%
See 1 more Smart Citation